Model Video Pembelajaran IPA Pada Kelas IV - Wanda Wahyu Melani; M. Tahir; Baiq Niswatul Khair (Journal of Classroom Action Research, 2022)
This research is a descriptive research which aims to describe the science learning video model in class IV and the steps for using the science learning video model. Educational media are used in the context of communication and interaction between teachers and students in the learning process, 1) story learning videos, 2) news learning videos, 3) presentation learning videos, 4) documentary learning videos. Based on the results of previous research in grade IV at SDN 19 Cakranegara, it was found that teachers at SDN 19 Cakranegara had used learning videos when delivering subject matter. Based on the results of interviews and observations that have been made, it is applied in order to create a more active learning atmosphere and train students to understand science lessons well and can apply them in everyday life, meaning that here it is very helpful in conveying practical problem material and also students quickly understand science lessons. Then the steps, 1) preparation of the learning video, preparing and adjusting the material to be delivered, 2) implementing the media, first arranging the seats, and delivering the material, then being ordered to do the task, 3) ending the learning video by giving assignments according to what that had been studied at that time. In learning science at SDN 19 Cakranegara, not every meeting uses the media, depending on the subject matter. Students are very active in following ongoing lessons, because students themselves do not feel bored because they only use books as media, besides that student get additional insight about the subject matter. Teaching and learning activities at SDN 19 Cakranegara are innovatively designed so that the data achieve the desired goals. The teaching and learning process is not only carried out using the classical system but has implemented independent learning and can solve its own problems from various problems encountered in learning.